Does E-Filing Reduce Tax Compliance Costs in Developing Countries? - Coolidge, Jacqueline; Yilmaz, Fatih (World Bank Group, Washington, DC, 2014)
As the use of e-fi ling of tax returns has spread from developed to developingcountries, it has been clear that this sort of reform can reduce errors and opportunities for corruption. Also, it has been widely assumed that taxpayercompliance costs would decrease with the use of e-fi ling, because less time isspent getting tax returns from the taxpayer to the revenue authority. This notesummarizes findings from tax compliance cost surveys and offers a cautiouslypositive assessment of e-fi ling reforms in developing countries with a numberof caveats. Countries should not rush to push e-fi ling on all taxpayers untilthe revenue authorities, infrastructure, and taxpayers are ready.